Study into the Impact of the Pandemic on Travel Patterns within the Metropolitan Area of Rio de Janeiro - Eunice Horácio de Souza de Barros Teixeira Rodrigues; Larissa Rodrigues Turini; Joyce Azevedo Caetano; Marina Leite de Barros Baltar; Cintia Machado de Oliveira; Glaydston Mattos Ribeiro; Rômulo Dante Orrico Filho (Urban Science, 2024)
Despite the ending of social distancing and post-pandemic return to normal activities, the impacts of COVID-19 on urban mobility persist, particularly with regard to public transport. Consequently, this study looks into the post-pandemic changes in travel patterns, seeking to comprehend the effects on the municipalities and suggest helpful measures geared to achieving more sustainable patterns following the lockdown isolation. The chosen case study is the Metropolitan Area of Rio de Janeiro, Brazil. The study was divided into four distinct phases, namely understanding the problems, choosing the study area, field research and making recommendations based not only on the literature but on consultation with operators and experts. The methodological process involves the analysis of data from the field research, to assess any changes in patterns that may have been identified. The results show the changes in the means of travel, with emphasis on a preference for app-based transport services, to the detriment of sustainable transport. The study also shows the challenges facing public transport and the relationship between the choice of travel means and the socioeconomic profile of the passenger.